A Gothic masterpiece in the Levant. Saint Nicholas Cathedral, Famagusta, North Cyprus - Walsh, M (Editions Scientifiques Medicales Elsevier, 2005)
This article presents a very brief historical overview, and contemporary description, of the Cathedral of St. Nicholas in Famagusta in Northern Cyprus. In the light of the changing political situation in that island it invites scholarship in a range of disciplines to the cathedral and to other historic landmarks within the old city walls. Scholars interested might include: art historians, architectural historians, civil engineers, archivists, historians, structural analysts, masonry conservators, surveyors, ecclesiastical historians, and a wider range of experts involved in the full study of other Gothic cathedrals elsewhere in mainland Europe. (c) 2005 Elsevier SAS. All rights reserved.
Keywords: Cyprus; Gothic; Lusignan; conservation; Annan; St. Nicholas; Famagusta; cathedral; medieval